Foetal hypoxia impacts methylome and transcriptome in developmental programming of heart disease. Issue 8 (5th November 2018) - Huang, Lei; Chen, Xin; Dasgupta, Chiranjib; Chen, Wanqiu; Song, Rui; Wang, Charles; Zhang, Lubo
Abstract : Aims: Antenatal hypoxia negatively impacts foetal heart development, and increases the risk of heart disease later in life. The molecular mechanisms remain largely elusive. Here, we conducted a genome-wide analysis to study the impact of antenatal hypoxia on DNA methylome and transcriptome profiling in foetal and adult offspring hearts. Methods and results: Pregnant rats were treated with normoxia or hypoxia (10.5% O2 ) from Day 15 to Day 21 of gestation. Hearts were isolated from near-term foetuses and 5-month-old male and female offsprings, and DNA methylome and RNA-seq were performed. Methylome data shows a sharp dip in CpG methylation centred at the transcription start site (TSS). CpG islands (CGIs) and CpG island shores (CGSs) within 10 kb upstream of the TSS are hypomethylated, compared with CGIs and CGSs within gene bodies. Combining transcriptome, data indicate an inverse relation between gene expression and CpG methylation around the TSS. Of interest, antenatal hypoxia induces opposite changes in methylation patterns in foetal and adult hearts, with hypermethylation in the foetus and hypomethylation in the adult. Also, there is significant sex dimorphism of changes in gene expression patterns in the adult offspring heart. Notably, pathway analysis indicates that enrichment of inflammation-related pathways are significantly greater in the adult male heart than those in the female heart. Conclusion: Our study provides an initial framework and new insights into foetal hypoxia-mediated epigenetic programming of pro-inflammatory phenotype in the heart development, linking antenatal stress, and developmental programming of heart vulnerability to disease later in life. Graphical Abstract: